Predicted of production curve and persistensy by wood non-linier model on white Mojosari duck - Suparyanto, Agus; Prasetyo, L.H (Indonesian Journal of Animal and Veterinary Sciences, 2004)
Until recent, the biology data from white Mojosari duck have been never reported. Different from their sister, the brown Mojosari duck was establish for laying duck. Equation model of non-linier Wood was commonly used to predict the milk production curve. This method is possible for egg production of laying duck. The purpose of the research is understanding of production curve fitted and persistency. The data were collected from 39 birds of White Mojosari duck in Balitnak Ciawi. Four types of analysis data set, those are partial data (16 weeks), full data (52 week), collective and individual data of egg production. The equation of mathematic non-linier Wood is Y=AtBexp-kt by DUD method. The result show that egg production was 236 for 52 weeks record and twenty five percent were reached up than 290 eggs. Production trait will decrease on 4-5th month and after that slow up for increasing, but never came as high as the first and second month production. Estimation of A parameter is 5.5- 6.9 eggs per week, meanwhile the constantan of B is 1.0-1.1 and k is 0.007-0.02 respectively for production data. By percent, showed that A (83-84%), B (0.02-0.06) and k (0.006-001), that all for partial and full data. Genetic correlation between parameter A and B is negative, which is 0.94â0.098 (production data) and 0.24-0.76 respectively. Positive correlation was resulted between B and k parameters. But for A and k parameters were both are positive and negative result. Estimation of persistency was 3.8 weeks for individual data and 3.7 weeks for collective data by partial (16 weeks) data set. And than the fulldata (52 weeks) are 4.0 and 4.1 respectively for collective and individual data set. Â  Key words: White Mojosari duck, non-linear, production curve